High-Sensitive C-Reactive Protein Predicts Recurrent Stroke and Poor Functional Outcome: Subanalysis of the Clopidogrel in High-Risk Patients With Acute Nondisabling Cerebrovascular Events Trial. Issue 8 (August 2016) - Li, Jiejie; Zhao, Xingquan; Meng, Xia; Lin, Jinxi; Liu, Liping; Wang, Chunxue; Wang, Anxin; Wang, Yilong; Wang, Yongjun
Abstract : Background and Purpose—: Minor stroke and transient ischemic attack are common disorders with high rate of subsequent disabling stroke. We aim to investigate the role of high-sensitive C-reactive protein (hsCRP) in predicting recurrent stroke and poor functional outcome. Methods—: In the Clopidogrel in High-Risk Patients With Acute Nondisabling Cerebrovascular Events (CHANCE) trial, 3044 (59%) consecutive patients from 73 (64%) prespecified centers had hsCRP levels measured. The primary outcome was any stroke within 90 days. The secondary outcome included combined vascular events and dependence or death defined as modified Rankin Scale score of 2 to 6 at 90 days and a new vascular event during 1-year follow-up. The associations of hsCRP with recurrent stroke and functional outcome were analyzed by using Cox proportional hazards and logistic regression models. Results—: Elevated hsCRP (>3.0 mg/L) was observed in 32% of the study population. Patients with hsCRP >3 mg/L had an increased risk of recurrent stroke (adjusted hazard ratio, 1.46; 95% confidence interval, 1.08–1.98; P =0.039), ischemic stroke and combined vascular events, and poor functional outcome (adjusted odds ratio, 1.68; 95% confidence interval, 1.22–2.32; P =0.002) compared with those with hsCRP <1 mg/L within 90-day follow-up period. High hsCRP levels also independently predicted recurrent stroke during 1-year follow-up. There was no interaction of hsCRP levels with randomized antiplatelet therapy. Conclusions—: High hsCRP levels predict recurrent stroke and poor functional outcome in acute patients with minor stroke or transient ischemic attack. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00979589. Abstract : Supplemental Digital Content is available in the text.